2 - Internet and Development in Senegal: Towards New Forms of Use - Christian Agbobli, (Africa Media Review, 2008)
This article addresses forms of Internet use within the framework of a development project. Through use of a case study of four telecentres set up by the Acacia initiative of Canada’s International Development Research Centre (IDRC), the article presents the theoretical claims of Internet use for development and determines the impact of the Internet on members of Senegalese economic and popular organisations. In this sense, the telecentre project reflects the tendency of international development to regard the Internet as a new and efficient strategy. However, the article asserts that only concrete uses demonstrate the role of the Internet in development. Traditional Internet uses – electronic mail and navigation – do appear. However, the results show a broader dimension of use that includes the appropriation of the telecentre itself and they advance the recognition of the presence of traditional communication as a complimentary element to Internet use. The article concludes that the local context and culture must be integrated into Internet use as a development strategy.